2022
DOI: 10.1227/ons.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Surgically Managed Spontaneous Spinal Epidural Hematoma: A Single-Center Case Series of 18 Patients

Abstract: BACKGROUND:Spontaneous spinal epidural hematoma (SSEH) is a rare pathology, which carries a significant morbidity.OBJECTIVE:To review our institutional experience of surgically managed patients with SSEH, seeking to better understand clinical prognostic factors related to postoperative outcomes and thereby improve counseling of patients before treatment.METHODS:All patients who underwent surgical management of SSEH between September 2011 and 2021. Baseline and postoperative clinical and radiological characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mohamed et al [ 6 ] also concluded that implantation of closed-suction drainage resulted in less formation of epidural fibrosis in patients operated on for unilateral, single-level lumbar disc hernias. Previous studies reported that multilevel procedures, deficient coagulation factors, decreased hemoglobin, advanced age, excessive drinking and previous spinal surgery were identified as risk factors for developing a postoperative epidural hematoma [ 32 35 ]. Therefore, these factors should be considered when deciding whether to use a drain tube after pedicle screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed et al [ 6 ] also concluded that implantation of closed-suction drainage resulted in less formation of epidural fibrosis in patients operated on for unilateral, single-level lumbar disc hernias. Previous studies reported that multilevel procedures, deficient coagulation factors, decreased hemoglobin, advanced age, excessive drinking and previous spinal surgery were identified as risk factors for developing a postoperative epidural hematoma [ 32 35 ]. Therefore, these factors should be considered when deciding whether to use a drain tube after pedicle screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…According to research, surgery within 36 h of symptom onset could achieve better outcomes in patients with complete loss of preoperative neurological function [22] . On the other hand, the ratio of recovery to normal can reach 95% for patients with incomplete loss of preoperative neurological function [23] .…”
Section: Discussionmentioning
confidence: 99%